The Effect of Substitution of Coarse and Fine Aggregates with Shells of Blood Clams and Cement With Fly Ash and The Additional of Superplasticizer Against The Compressive Test - Syafwandi Syafwandi; Ryan Adisya Cerra (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Concrete generally composed of four main constituent materials namely portland cement, fine aggregate (sand), coarse aggregate (gravel), and water. The large amount of use of concrete in construction results in an increase in the demand for concrete materials, thus triggering the mining of concrete materials on a large scale which caused the decline in natural resources in Indonesia for the need for concrete material. If needed, substitute materials can be created in such a way as to change certain properties of concrete to function better, economically, and environmentally friendly. The waste of fly ash and shells of blood clams can be used as a substitute for cement, coarse aggregates and fine aggregates. The purpose of this research is to determine the compressive strength of the variation of the percentage of fly ash substitution with cement and shells of blood clams with coarse and fine aggregates and the addition of superplasticizer to the compressive strength of concrete. The research is using experimental methods, test specimen samples will be tested for workability, density, and compressive strength. Variable in the research are (1) related variables : density and compressive strength, (2) independent variable : variation of 0%, 5%, 10%, and 15% of blood clam shell needs of the total weight of coarse aggregate. Based on the results of the research concluded that (1) Slump value of the samples 0%, 5%, 10%, and 15% consecutive is 97mm, 89mm, 151mm, 149mm. (2) density of concrete with substitution of blood clam shells with coarse aggregate with samples 0%, 5%, 10%, and 15% consecutive is 2284 Kg/m3, 2308 Kg/m3, 2297 Kg/m3, and 2293 Kg/m3. (3) Testing of concrete compressive strength at 28 days with substitution of blood clam shells with coarse aggregate with samples 0%, 5%, 10%, and 15% consecutive is 21.44 Mpa, 24.38 Mpa, 19.02 Mpa, and 19.34 Mpa. The composition of substitution of blood clam shells with coarse aggregate of 5% has a higher compressive strength than other compositions.